2017
DOI: 10.1038/tp.2017.133
|View full text |Cite
|
Sign up to set email alerts
|

Serotonin transporter gene promoter methylation status correlates with in vivo prefrontal 5-HTT availability and reward function in human obesity

Abstract: A polymorphism in the promoter region of the human serotonin transporter (5-HTT)-coding SLC6A4 gene (5-HTTLPR) has been implicated in moderating susceptibility to stress-related psychopathology and to possess regulatory functions on human in vivo 5-HTT availability. However, data on a direct relation between 5-HTTLPR and in vivo 5-HTT availability have been inconsistent. Additional factors such as epigenetic modifications of 5-HTTLPR might contribute to this association. This is of particular interest in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 71 publications
(84 reference statements)
0
13
0
Order By: Relevance
“…However, accumulating evidence points to peripheral methylation patterns to constitute valid proxies for central processes (see, e.g., Ursini et al, 2011 ; Davies et al, 2012 ; Provencal et al, 2012 ). With regard to SLC6A4 , employing PET, methylation levels measured in peripheral cells were shown to be inversely related to 5-HT synthesis ( Wang et al, 2012 ) and 5-HTT availability ( Drabe et al, 2017 ) in the human brain, supporting the notion of peripheral SLC6A4 methylation to possibly mirror central processes.…”
Section: Discussionmentioning
confidence: 76%
“…However, accumulating evidence points to peripheral methylation patterns to constitute valid proxies for central processes (see, e.g., Ursini et al, 2011 ; Davies et al, 2012 ; Provencal et al, 2012 ). With regard to SLC6A4 , employing PET, methylation levels measured in peripheral cells were shown to be inversely related to 5-HT synthesis ( Wang et al, 2012 ) and 5-HTT availability ( Drabe et al, 2017 ) in the human brain, supporting the notion of peripheral SLC6A4 methylation to possibly mirror central processes.…”
Section: Discussionmentioning
confidence: 76%
“…The serotonin transporter is a key regulator of 5-HT levels, and its function is affected by epigenetic mechanisms including methylation of the SLC6A4 gene 21 , 40 . Hypermethylation of the SLC6A4 gene was associated with decreased SLC6A4 mRNA 13 , 21 , gene activity 40 , brain 5-HT synthesis 21 , and availiability 41 . Stroke patients with SLC6A4 hypermethylation might have reduced 5-HTT function and 5-HT availability, which would lead to decreased BDNF expression and thus suppress neurogenesis 42 , 43 and promote inflammation 44 .…”
Section: Discussionmentioning
confidence: 97%
“…Our findings suggest that methylation and SI might have synergistic effects on long-term stroke outcomes. Previously, suicidality was shown to be associated with low 5-HT 22 , and SLC6A4 hypermethylation would exacerbate any deficit in 5HT 21 , 41 . Furthermore, post-stroke depression (PSD) is a well-known risk factor for poor long-term stroke outcomes 52 , and SI after stroke is strongly associated with PSD 30 , 45 and SLC6A4 hypermethylation has been proposed as a diagnostic and prognostic biomarker for PSD 34 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Wang et al 11 found that SLC6A4 promoter methylation in T lymphocytes of adults was associated with lower in vivo Positron Emission Tomography (PET) measures of brain serotonin (5-hydroxytryptamine; 5-HT) synthesis in the orbitofrontal cortex and higher childhood aggression. Furthermore, a recent study found associations between SLC6A4 methylation and in vivo PET measures of serotonin transporter availability 12 . We also previously reported that SCL6A4 methylation obtained from white blood cells was significantly associated with activation in response to negative emotional stimuli in the insula 13 and lower hippocampal volume 14 in depressed patients and controls.…”
Section: Introductionmentioning
confidence: 99%